Efektivitas Gereja Dalam Menuntaskan Amanat Agung - Samuel Purdaryanto (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2021)
The church is a collection of believers who have been called from darkness to light to belong to God and to be witnesses in the midst of the world. As God's representative in the world, the church carries out the Great Commission mandated by the Lord Jesus to make all ethnic groups disciples of Christ. The Bible records that the early church or the early birth of the church there was a tremendous multiplication movement. Starting from 120 disciples then 3000 and then there were many people who believed in Christ and became His disciples. However, the situation changed after 313 or after the Edict of Milano, the missionary movement of evangelism was no longer like the era of the early church. The church spends more of its time resolving internal conflicts. These changes are still happening today, and in the end the church has become less effective in completing the Great Commission. The church is still busy in resolving internal conflicts, building elephant churches, not adopting unreach people groups and even not making disciples. The church must adapt in order to be effective in accomplishing the Great Commission. Build a missionary church, send, disciple and multiply. So that the church becomes effective in completing the Great Commission of the Lord Jesus.